The Effect of Academic Stress on Smartphone Addiction on Students in Medan - Fikri Azriel Akbar Siregar; Nurussakinah Daulay (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
This research article discusses academic stress that occurs in the lives of students during the pandemic and the alleged role of smartphones as the impact of stress they face. The purpose of this study was to determine the effect of academic stress on smartphone addiction in MTs NII students in Medan City. Quantitative is the method used in this research. A total of 170 students were selected as subjects with quota sampling technique. Data were collected using the academic stress scale and the smartphone addiction scale. The data that has been collected is then analyzed using a linear regression analysis test. The results of this study found that there was a significant influence between academic stress on smartphone addiction. Data calculation analysis was performed using the SPSS 25 statistical program for Windows. The results prove that there is a significant relationship between Academic Stress and Smartphone Addiction, then from the analysis carried out there is a value (R: 0.602 and P: 0.000 <0.050). The contribution of the influence of academic stress on smartphone addiction in MTs NII students in Medan is 60.2 percent.